The influence of service quality and company reputation on purchase decisions with customer experience as moderators in creative industrial companies - Andarina, Deansha Ghaisani; Kodrat, David Sukardi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
This research has purpose to determine the effect of service quality and company reputation on purchasing decisions with customer experience as a moderator in a creative industry company at PT. Rangkai Cipta Kreasi. The method used in this research is a quantitative approach. The number of samples used was 65 respondents, taken using purposive sampling technique. The results of the study revealed that service quality and company reputation have a positive effect on purchasing decisions. Customer experience does not act as a moderator of the influence of quality on service quality but strengthens the influence of company reputation on purchasing decisions.